"How" and "Why" prompts in forensic investigative interviews with preschool children. Issue 1 (2nd January 2017) - Malloy, Lindsay C.; Orbach, Yael; Lamb, Michael E.; Walker, Anne Graffam
ABSTRACT: Although young children may frequently be asked "How" and "Why" questions, it is unclear whether they have the ability to respond well enough to justify the use of these words during investigative interviews. The range of possible uses and interpretations of the words "How" and "Why" makes it critical to examine their use when communicatively immature children are interviewed. In this study, police interviews of 3- to 5-year-old suspected victims of sexual abuse ( n = 49) were examined. The use of How/Why prompts by interviewers and children's responses to interviewers' How/Why prompts were coded. How/Why prompts represented 22% of all interviewer prompts. Of all details provided by children, however, 8.5% were in response to How/Why prompts. In addition, children provided the information sought in response to only 20% of the interviewers' How/Why prompts, whereas uninformative responses were relatively common. Children responded to more How/Why prompts with the information sought by interviewers as they grew older. The findings suggest that How/Why prompts may not be particularly effective when interviewing preschool children.